Transformation of agricultural landscapes in the Anthropocene: Nature’s contributions to people, agriculture and food security - Vanbergen, Adam J. (2020)
Fil: Vanbergen, Adam J. Université de Bourgogne Franche-Comté. AgroSup Dijon. Agroécologie. Francia.